Investigation of the relationship of frontal QRS-T angle and digoxin use and blood digoxin level - Zengin, İsmet and Uğuz, Berat (The European Research Journal, 2022)
Objectives: Digoxin is an antiarrhythmic drug with a narrow therapeutic range and used in clinical conditions such as heart failure and atrial fibrillation. The planar frontal QRS-T angle reflects the deviations between the depolarization and repolarization of the ventricles, and it has been reported that an increase in this angle is associated with an increase in mortality. In our study, the relationship between frontal QRS-T angle and digoxin use and blood digoxin level was investigated. Methods: The study included 105 digoxin users who used digoxin, whose levels were measured, who had an electrocardiogram (ECG) on the system, and 15 patients with similar characteristics, who had an ECG and did not use digoxin. Patients using digoxin and whose levels were measured were also divided into three groups as < 0.8 ng/mL, 0.8-1.2 ng/mL, and > 1.2 ng/mL. The absolute value of the value obtained by subtracting the axis of the T wave from the axis of the QRS angle indicated on the paper, calculated automatically on the 12-lead ECG, was accepted as the frontal QRS-T angle value. Results: Planar frontal QRS-T angle measured by 12-lead ECG in digoxin users was 120º (55.5º-155.5º), while it was 106º (32º-163º) in non-users, and there was no statistical difference between the two groups (p = 0.833). In the evaluation made according to different blood drug levels as < 0.8 ng/mL, 0.8-1.2 ng/mL, > 1.2 ng/mL in digoxin users, no significant difference was observed between the frontal QRS-T angle between the groups (109.5° [60.25°-154.25°] for < 0.8 ng/mL, 136.5° [48.5°-158.5°] for 0.8-1.2 ng/mL, 117° [34°-154°] for 1.2 ng/mL) (p = 0.773). Conclusions: There was no significant difference in frontal QRS-T angle between digoxin users and non-users. There was no significant relationship between different blood digoxin levels and frontal QRS-T angle.